Disparities in black and white patients with multiple myeloma referred for autologous hematopoietic transplantation: A single center study. Issue 7 (2nd December 2014) - Bhatnagar, Vishal; Wu, Yin; Goloubeva, Olga G.; Ruehle, Kathleen T.; Milliron, Todd E.; Harris, Carolynn G.; Rapoport, Aaron P.; Yanovich, Saul; Sausville, Edward A.; Baer, Maria R.; Badros, Ashraf Z.
<x xml:space="preserve">Abstract</x> Background Racial disparity in the incidence of multiple myeloma is well established; however, to the authors' knowledge, little is known regarding the impact of racial differences on disease characteristics, response to therapy, and clinical outcome. Methods The authors studied 453 patients (174 of whom were black and 279 of whom were white) who underwent transplant between 2000 and 2013. The median follow‐up was 4.4 years. Results Black patients were significantly younger than white patients (median age, 54 years vs 59 years; P<.0001), more frequently presented with anemia (P = .04), had more of the immunoglobulin G isotype (P<.001), and had a borderline favorable cytogenetic risk (P = .06). Overall response to induction was similar, but deeper responses were observed in more white patients compared with black patients receiving immunomodulatory drug‐based induction (P = .02). Referral for transplant was significantly delayed in black individuals (median, 1.3 years vs 0.9 years; P = .003). Overall survival from the time of transplant was similar for black and white patients, with medians of 6.2 years and 5.7 years, respectively, but survival from the time of diagnosis was significantly longer among black individuals (median, 7.7 years vs 6.1 years; P = .03). Maintenance therapy was found to positively impact progression‐free survival but not overall survival, irrespective of race. Conclusions The results of the current study confirm ethnic differences in age, referral patterns, response to therapy, and overall survival. Future validation of these disparities is urgently needed. Cancer 2015;121:1064–1070. © 2014 American Cancer Society.